'Thanks to Corona virus': trajectories of masculinities during the Ugandan lockdown. Issue 3 (3rd July 2021) - Baral, Anna
ABSTRACT: The restrictions to curb the Covid-19 pandemic have caused an escalation of gender-based violence all over the world, but they have also changed the trajectories of masculinities in nuanced and complex ways. In this article, I explore the experiences of Ugandan men who became unable to provide under the national lockdown, often finding themselves confined in their homes for the first time in their life. I discuss two dimensions of this experience. On the one hand, men had to painfully withdraw from circles of reciprocity, exemplified by the practice of 'checking on', too burdensome in a moment of economic insecurity. On the other hand, men's 'being there', at home, progressively shifted from an unwanted obligation to a welcomed responsibility, embraced intentionally. Juggling between forced proximity and distance, men explored different ways of validating themselves in the crisis. They both reproduced pre-existing dynamics, grounded on the tension between provision and withdrawal, and experienced emergent forms of caring masculinities and fatherhood, performed through sharing and reciprocity.